Social brain matters : stances on the neurobiology of social cognition - Vilarroya, Òscar.; Forn i Argimon, Francesc. (Value Inquiry Book Series, 2007)
This book examines philosophical and scientific implications of Neodarwinism relative to recent empirical data. It develops explanations of social behavior and cognition through analysis of mental capabilities and consideration of ethical issues. It includes debate within cognitive science among explanations of social and moral phenomena from philosophy, evolutionary and cognitive psychology, neurobiology, linguistics, and computer science. The series Cognitive Science provides an original corpus of scholarly work that makes explicit the import of cognitive-science research for philosophical analysis. Topics include the nature, structure, and justification of knowledge, cognitive architectures and development, brain-mind theories, and consciousness.